Peningkatan Kesadaran dan Deteksi Dini Faktor Risiko Penyakit Tidak Menular Melalui Skrining Kesehatan Terintegrasi - Githa Agripina Barokah; Renisa Renisa; Asri Zahra Meirina; Linda Yulianti Maulidah; Ananda Mutiara Zahirah; Fahmi Al Jaelani; Muhammad Shofaruddin; Mia Sumiati; Intan Rahmawati; Fera Srihandayani; Aneng Yuningsih (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Non-communicable diseases (NCDs) remain a major public health problem due to low awareness of early detection and prevention. Hypertension and diabetes mellitus often occur without symptoms and may lead to severe complications. In addition, visual impairment caused by refractive disorders can reduce quality of life and productivity. Integrated health screening and education are important strategies to improve community awareness and early detection of health problems. Objective: This community service activity aimed to improve early detection of NCD risk factors and visual impairment through integrated community-based health screening and education. Method: The activity was conducted in RT 01 RW 09 Kersanagara, Tasikmalaya City, involving 35 respondents selected through purposive sampling. The program included blood pressure measurement, blood glucose testing, visual acuity examination, and health education regarding healthy lifestyles and NCD prevention. Knowledge improvement was evaluated using pre-test and post-test questionnaires. Result: The results showed that 11.4% of respondents had hypertension and 20% had elevated blood glucose levels. Visual screening identified hypermetropia (11.4%), myopia (8.6%), astigmatism (2.9%), and cataracts (2.9%). Health education improved participants’ knowledge, with correct responses increasing from 87.43% in the pre-test to 97.14% in the post-test. Conclusion: Integrated screening and health education effectively improved early detection of NCD risk factors and increased community health awareness.